PERANCANGAN DAN ANALISIS SISTEM PLTS UNTUK ALAT PEMBUAT PAKAN TERNAK - Budiman, Injilia Tezalonika; Kures, Yansen Gerral Adriano Marthen; Namangge, Desi Steni; Atmaja, I Gede Para (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The growing demand for efficient and sustainable animal feed production in rural areas underscores the need for a reliable, energy-independent feed-making system. This study aims to design and develop a livestock feed-making machine integrated with a Solar Power Plant (PLTS) as its primary energy source, enabling fully autonomous operation without dependence on the conventional electricity grid. An experimental design and prototyping approach was adopted, covering system design, component specification, and technical calculation. The system consists of solar panels, a battery bank, a Solar Charge Controller (SCC), and an electric motor drive. Based on a total daily energy requirement of 3,210 Wh, the designed system employs five 140 Wp solar panels, a 48V/100 Ah battery, and a 20A SCC. The calculation results show that the designed system is theoretically capable of supplying sufficient energy for fully autonomous operation, offering a practical and environmentally friendly solution for farmers in areas with limited grid electricity access.